A bounded-error approach to actuator fault diagnosis and remaining useful life prognosis of Takagi-Sugeno fuzzy systems. (September 2018) - Mrugalska, Beata
Abstract: The paper presents an actuator fault diagnosis and prognosis scheme for Takagi-Sugeno fuzzy system. It overcomes the drawbacks of the approaches presented in the relevant literature by taking into consideration the problem of the robustness. The proposed approach consists of an actuator fault estimator which provides knowledge about faults with their uncertainty intervals. Thus, the fault detection mechanism relies on an acceptable threshold imposed on these intervals. Once the fault is detected, the remaining useful life of an actuator is predicted what is expressed in the so-called time-to-failure. Similarly as in the case of fault estimation, the remaining useful life is provided as an uncertainty interval. It should be notated that previously reported approaches to Takagi-Sugeno systems cannot either provide the uncertainty of fault estimates for remaining useful life. To tackle the development of the above schemes the theory of quadratic boundedness and feasible parameter set-based estimation are employed. The final part of the paper portrays a case study which clearly exhibits the performance of the proposed approach. Graphical abstract: Highlights: Fault diagnosis and time to failure prognosis for nonlinear systems modelled with the Takagi-Sugeno scheme. Robust actuator fault estimation in the form of the uncertainty intervals. Robust approach to prediction of the actuator remaining useful life in the form of Time-To-Failure uncertainty interval. Prospective application of the proposed approach to fault-tolerant control.